Community Empowerment as a National Priority in Development - Wafa Adila; Ernita Puspa Dewi; Hosnul Khotimah Lestari (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2023)
Community empowerment is a fundamental pillar of national development aimed at enhancing social welfare, social justice, and active public participation in the development process. This Community Service Program aims to strengthen community understanding and capacity, particularly among women members of the PKK organization in Rimba Sekampung Village, regarding the strategic role of community empowerment as a national development priority. The activity was conducted on Thursday, January 18, 2024, at Jalan Belimbing, Rimba Sekampung Village, Dumai City. The implementation method employed socialization through counseling and persuasive guidance using a non-formal and participatory educational approach. The program focuses on women's empowerment, community participation in development, and the prevention of social issues such as sexual violence and bullying among children and adolescents. The results indicate an improvement in participants' awareness, understanding, and active involvement during discussions, as well as a strengthened commitment to act as agents of change within their communities. This program contributes positively to reinforcing the role of women as strategic partners of the government in promoting inclusive, equitable, and sustainable national development.